Transcriptome analysis reveals that PRV XJ delgE/gI/TK protects against intestinal damage in nose-dropping-infected mice by regulating ECM-ITGA/ITGB-P-FAK - Tong Xu; Yang Zhang; Qian Tao; Lei Xu; Si-Yuan Lai; Yan-Ru Ai; Jian-Bo Huang; Ben-Lu Yang; Ling Zhu; Zhi-Wen Xu (Microbiology Spectrum)
ABSTRACT Pseudorabies virus (PRV) is an ideal model for mechanistic investigations into α-herpesvirus. The neurotropism and latent infection of PRV have been extensively studied. Apart from neurological symptoms, diarrhea caused by PRV infection is also an essential cause of mortality in newborn and weaned piglets. However, little research has been done on PRV invasion of the gut. To fill this gap, a nasal drip PRV-infection mouse model was developed, consisting of three groups: the challenged group (Group A), the immunization-challenged group (Group B), and a mock group (Group C). The results showed that immunization with PRV XJ delgE/gI/TK successfully prevented intestinal damage caused by PRV drop-nose infection. Subsequently, intestines were collected for transcriptional analysis. Differentially expressed genes analysis revealed that PRV XJ delgE/gI/TK was effective in reducing the organismal intestinal transcriptional activity caused by PRV. The Group A vs Group C and Group A vs Group B had similar Kyoto Encyclopedia of Genes and Genomes (KEGG)-enriched signaling pathways and the differentially expressed genes were primarily enriched in pathways, such as cell adhesion molecules, focal adhesion kinase, and actin cytoskeleton regulation. Notably, transcriptome analysis indicated that genes associated with the focal adhesion kinase (FAK) signaling pathway (ECM-ITGA/ITGB-p-FAK) were significantly more highly expressed in Group A than in Group B and Group C. The results of quantitative real-time PCR (RT-qPCR) and western blotting were consistent with KEGG analysis. Therefore, we hypothesized that PRV promotes self-infection through activation of the ECM-ITGA/ITGB-p-FAK signaling pathway and that PRV XJ delgE/gI/TK immunization could attenuate the intestinal damage caused by PRV by inhibiting the activation of this pathway.IMPORTANCEPseudorabies virus (PRV) poses a significant threat to the swine industry and public health due to its ability to infect multiple species, including humans, leading to substantial economic losses and potential health risks. This study addresses a critical gap in understanding the impact of PRV infection on the gut, which has been less explored compared to its neurological effects. By developing a drip-nose PRV-infection mouse model, the research indicated that PRV might promote self-infection through activation of the ECM-ITGA/ITGB-p-FAK signaling pathway, and PRV XJ delgE/gI/TK immunization effectively prevents intestinal damage by significantly reducing the expression of genes in the ECM-ITGA/ITGB-p-FAK signaling pathway. The research has important implications for the swine industry and public health by contributing to the development of better vaccines and treatments, ultimately helping to control PRV and prevent its cross-species transmission.